1970
DOI: 10.4039/ent1021554-12
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Technique for Mass-Rearing the Onion Maggot (Diptera: Anthomyiidae) on an Artificial Diet

Abstract: Can. Ent. 102: 1554-1558 (1970) A gelatine-based diet for rearing the onion maggot, Hylemya antiqua (Meigen), that contains sucrose, evaporated milk, yeast hydrolysate, wheat embryo, cellulose powder, n-propyl disulfide, water, and antibiotics is described. Three consecutive generations reared on this medium were equal in puparial weights, percentages of pupation, adult emergence, and egg hatch, to those reared on onion bulbs. The procedure is simple and two man-hours per week is sufficient for producing 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1977
1977
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 10 publications
0
0
1
Order By: Relevance
“…While we found that protein-deprivation did not inhibit male reproductive competency over 24 h, the addition of protein to carbohydrate diet significantly enhanced male survivorship, which we believe could affect lifetime reproductive success (Figure 4). Maximum survivorship and median life expectancy of males provided with a mixture of carbohydrate and protein in our study was considerably longer (91 and 38 days, respectively) than previous records of maximum longevity for males maintained on similar diet in the laboratory or in field cages [41-70 days, (Allen & Askew, 1970;Vernon & Borden, 1979) and ca. 33 days (Perron & Lafrance, 1961), respectively].…”
Section: Discussioncontrasting
confidence: 64%
“…While we found that protein-deprivation did not inhibit male reproductive competency over 24 h, the addition of protein to carbohydrate diet significantly enhanced male survivorship, which we believe could affect lifetime reproductive success (Figure 4). Maximum survivorship and median life expectancy of males provided with a mixture of carbohydrate and protein in our study was considerably longer (91 and 38 days, respectively) than previous records of maximum longevity for males maintained on similar diet in the laboratory or in field cages [41-70 days, (Allen & Askew, 1970;Vernon & Borden, 1979) and ca. 33 days (Perron & Lafrance, 1961), respectively].…”
Section: Discussioncontrasting
confidence: 64%